Sorogan-Based Learning to Stimulate Early Counting Skills - Komara, Osfir Candikia Rara; Sumaji; Wahyudi; Qoyyimuddin, Ahmad Azzam Al (Journal for Lesson and Learning Studies, 2024)
Beginning counting ability is an important basic ability for students to be able to answer and understand further mathematical problems, including the introduction of numbers and basic mathematical concepts. The problem discussed here is an attempt to change the conventional teaching method (lecture) at the beginning counting learning stage towards a learning approach that can better facilitate children's learning needs and create meaningful learning. This study aims to analyze the application of the Sorogan method assisted by graded student worksheets (LKS) in stimulating student’s counting skills in Calistung class. The research method used is descriptive qualitative, with a case study approach. This research was conducted involving Calistung B class students consisting of 5 children as research subjects. The research techniques used were observation, interview, and documentation. The results showed that the Sorogan method assisted by graded worksheets was able to make a positive contribution in stimulating student’s beginning counting skills. Components such as initial apperception, practice problems, discussion, and reflection applied in Sorogan learning activities play an important role in supporting the formation of deep understanding. The student-centered learning process of the Sorogan method, which prioritizes a focus on exploring aspects of individuality, supported by the use of graded worksheets, gradually helps students understand numeracy concepts, thus becoming the foundation for the continuous development of numeracy skills. This method can be an alternative for educators to improve the quality of learning early counting.